A identidade socioespacial e a constituição territorial : o papel das dinâmicas econômicas na conservação do patrimônio - Nicolau, Alexandre Ricardo (2010)
This research is an approach to the urban trajectories of two Municipalities, Muqui Alegre. Analyzing the socio-spatial identities present in these municipalities, the study proposed here identifies the forms of adaptation and transformation of distinct n